Смерть со школьной скамьи: [роман] / Геннадий Сорокин - Сорокин Геннадий Геннадьевич (Детектив-Ностальгия, 2019)
Экземпляры: аб. ЦБ (20200818) / Инвентарный номер: 8016 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 65 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6